ENTERPRISE INFORMATION SYSTEMS ARCHITECTURE SUPPORTING E BUSINESS AND E GOVERNMENT DIGITAL TRANSFORMATION - Ryan Teo; Fatimah Fahurian; Triyugo Winarko (Journal of Computer Science Advancements, 2026)
The digital transformation of both e-business and e-government is increasingly dependent on the effective implementation of Enterprise Information Systems (EIS) architecture. As organizations seek to optimize their operations, enhance transparency, and improve service delivery, the need for robust EIS architectures has become critical. These architectures facilitate the integration of diverse systems, ensuring interoperability, scalability, and security. This study investigates how EIS architecture supports the digital transformation efforts in e-business and e-government, focusing on its impact on operational efficiency, data management, and stakeholder trust. A qualitative research design is employed, utilizing case studies, interviews, and document analysis from both public and private sector organizations. The findings reveal that EIS architecture significantly enhances the operational efficiency of both e-business and e-government, improving data security and reducing administrative bottlenecks. Institutions with fully integrated EIS reported improvements in service delivery, stakeholder satisfaction, and overall transparency. The research concludes that adopting modern EIS architectures is essential for successful digital transformation, particularly in sectors where data integrity and governance are paramount.